2006
DOI: 10.1897/05-405r.1
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of adsorption and desorption of some organochlorine compounds on black carbon in a sediment

Abstract: Rate constants for adsorption and desorption of four organochlorine compounds on black carbon in a sediment were determined from measurements of the rate of removal, by gas purge, of the organochlorine compounds as single solutes from a water-sediment mixture immediately after addition of the solute to the system. The rates of removal fitted to a kinetic scheme based on Langmuir adsorption onto two types of sites in black carbon. The first-order rate constants for desorption from these sites were comparable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
(39 reference statements)
3
13
0
Order By: Relevance
“…It is thought that this could be one of the factors that had an influence on the increase in the sorption amount by the bamboo charcoal. The sorption and desorption of organic compounds on sorptive building materials are determined by the gas-phase Langmuir isotherm equation [10,[31][32][33]. The HCHO saturation sorption values for the building materials was predicted by the Langmuir model when exposed in a HCHO concentration of 100 mg m -3 , which is the guideline value for HCHO set by WHO.…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that this could be one of the factors that had an influence on the increase in the sorption amount by the bamboo charcoal. The sorption and desorption of organic compounds on sorptive building materials are determined by the gas-phase Langmuir isotherm equation [10,[31][32][33]. The HCHO saturation sorption values for the building materials was predicted by the Langmuir model when exposed in a HCHO concentration of 100 mg m -3 , which is the guideline value for HCHO set by WHO.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that the hysteresis is most likely attributable to the entrapment of sorbing molecules within highly condensed organic carbon and to slow desorption (Ran et al, 2003;Vrind et al, 2006). In the desorption stage, the aqueous-phase solute concentration decreased abruptly, and rates of such diffusion processes became accordingly slower, which may result in apparent rate-related desorption hysteresis.…”
Section: Sorption and Desorption Isothermsmentioning
confidence: 99%
“…More recently, it was reported that the sorption of the sorbate molecules may cause the deformation of SOC, also resulting in sorptiondesorption hysteresis (Lu and Pignatello, 2002;Weber et al, 2002;Wu and Sun, 2010). As for the desorption, most studies had focused on the desorption kinetics (Vrind et al, 2006;Morelis and van Noort, 2008;Xu et al, 2010), of which experiments were carried out at a single-level initial HOC concentration. Hence, desorption isotherms could not be constructed, and the concentration dependence of desorption behavior was not investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The sorbent fractions in natural sediment consist of organic matters and inorganic matters, in which the solid organic matter (SOM) including amorphous organic carbon and condensed organic carbon is considered primarily to control the sorption of HOCs [2,4,5].…”
Section: Introductionmentioning
confidence: 99%